ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU PAKAN TERNAK AYAM DI PT KMS DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) DAN JUST IN TIME (JIT) - Arindi, Fayadira Dyah; Khaidjah, Afni; Gautama, Pugy (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2024)
This research purpose to calculate the optimal quantity of raw material orders for chicken animal feed and the number of ordering frequencies, calculate the total cost of raw material inventory for chicken animal feed, analyze the most efficient method that must be applied to minimize the cost of raw material inventory at PT Kerta Mulya Saripakan. The method used in this research is the Economic Order Quantity (EOQ) and Just In Time (JIT) methods. After done analysis, the cost of raw material supplies incurred by the company, calculated according to company policy, reached IDR 459,616,202. By using the Economic Order Quantity (EOQ) method, the total inventory cost is IDR 340,449,297. Meanwhile, using the Just In Time (JIT) method, the total inventory costs incurred were IDR. 218,939,956. So a method that can minimize inventory costs at PT. Kerta Mulya Saripakan uses the Just In Time (JIT) method.